ENHANCING ALUMNI PARTICIPATORY COMMUNICATION FOR PESANTREN'S ECONOMIC DEVELOPMENT: A CONCEPTUAL APPROACH - Ahmad Afif (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
This study aims to develop an effective participatory communication model between Islamic boarding schools and alumni in order to increase alumni involvement and support Islamic boarding schools' economic development. We used a descriptive-qualitative research method, which involves in-depth observation and data analysis. The research results show that ongoing communication between Islamic boarding schools and alumni still faces several obstacles, such as lack of access to technology, incomplete alumni data, and generational differences. However, there are great opportunities in the use of digital platforms, updating alumni databases, and developing interesting alumni programs. The implementation of this participatory communication model has resulted in a significant increase in alumni involvement, as well as strengthening financial and non-financial support for Islamic boarding schools. Evaluation of the impact of this communication model shows increased alumni participation in various Islamic boarding school activities, which contributes to the economic development of Islamic boarding schools more effectively and sustainably.